Taming the wild: resolving the gene pools of non-model Arabidopsis lineages - Hohmann, Nora; Schmickl, Roswitha; Chiang, Tzen-Yuh; Lučanová, Magdalena; Kolář, Filip; Marhold, Karol; Koch, Marcus A (BMC evolutionary biology, 2014)
BACKGROUND: Wild relatives in the genus Arabidopsis are recognized as useful model systems to study traits and evolutionary processes in outcrossing species, which are often difficult or even impossible to investigate in the selfing and annual Arabidopsis thaliana. However, Arabidopsis as a genus is littered with sub-species and ecotypes which make realizing the potential of these non-model Arabidopsis lineages problematic. There are relatively few evolutionary studies which comprehensively characterize the gene pools across all of the Arabidopsis supra-groups and hypothesized evolutionary lineages and none include sampling at a world-wide scale. Here we explore the gene pools of these various taxa using various molecular markers and cytological analyses. RESULTS: Based on ITS, microsatellite, chloroplast and nuclear DNA content data we demonstrate the presence of three major evolutionary groups broadly characterized as A. lyrata group, A. halleri group and A. arenosa group. All are composed of further species and sub-species forming larger aggregates. Depending on the resolution of the marker, a few closely related taxa such as A. pedemontana, A. cebennensis and A. croatica are also clearly distinct evolutionary lineages. ITS sequences and a population-based screen based on microsatellites were highly concordant. The major gene pools identified by ITS sequences were also significantly differentiated by their homoploid nuclear DNA content estimated by flow cytometry. The chloroplast genome provided less resolution than the nuclear data, and it remains unclear whether the extensive haplotype sharing apparent between taxa results from gene flow or incomplete lineage sorting in this relatively young group of species with Pleistocene origins. CONCLUSIONS: Our study provides a comprehensive overview of the genetic variation within and among the various taxa of the genus Arabidopsis. The resolved gene pools and evolutionary lineages will set the framework for future comparative studies on genetic diversity. Extensive population-based phylogeographic studies will also be required, however, in particular for A. arenosa and their affiliated taxa and cytotypes.
Keywords: fylogeografie; genom chloroplastový; biologická evoluce; Phylogeography; Gene Flow; ekotyp; mikrosatelitní repetice; genetická variace; chloroplasty; Biological Evolution; Microsatellite Repeats; Genetic Variation; Ecotype; tok genů; Genome, Chloroplast; Gene Pool; genový pool; Arabidopsis; Chloroplasts